2019
DOI: 10.1177/0145561319879245
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Evolution of Acute Oral Complications in Patients Undergoing Radiochemotherapy Treatment for Head and Neck Squamous Cell Carcinoma

Abstract: Despite its effectiveness, radiochemotherapy treatment in the head and neck region is accompanied by acute oral complications such as oral mucositis, dysphagia, xerostomia, and dysgeusia. The aim of this study was to analyze and prospectively assess the frequency and evolution of acute oral complications during radiochemotherapy in patients diagnosed with squamous cell carcinoma in the head and neck region. We have analyzed oral complications of 20 patients during 6 weeks of radiochemotherapy treatment for squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Another prevalent symptom related to those previously mentioned is sore throat (51.2%), which presents itself almost conjointly with decreased taste, which consequently leads to decreased saliva in the region, causing severe pain. Such findings in the present research have a high incidence and the literature reports that one adverse effect may trigger the others [19]. The difficulty in eating, also called dysphagia, results from anatomical changes and fibrosis due to radiation effects in the region.…”
Section: Discussionsupporting
confidence: 59%
“…Another prevalent symptom related to those previously mentioned is sore throat (51.2%), which presents itself almost conjointly with decreased taste, which consequently leads to decreased saliva in the region, causing severe pain. Such findings in the present research have a high incidence and the literature reports that one adverse effect may trigger the others [19]. The difficulty in eating, also called dysphagia, results from anatomical changes and fibrosis due to radiation effects in the region.…”
Section: Discussionsupporting
confidence: 59%
“…As oral health implies the maintenance of a complex microbiotic equilibrium, fluctuations in the availability of oxygen, nutrients, and the pH-mediating effect of saliva can result in the growth of some microorganisms and further cause opportunistic infections [ 3 , 4 , 7 , 20 ]. Such changes may occur in immunosuppressed individuals, patients undergoing radiotherapy, chemotherapy, prolonged antimicrobial therapy, and steroid administration, and people suffering from xerostomia, diabetes, or cancer [ 3 , 7 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Nonetheless, otherwise healthy individuals may develop oral infections due to a series of risk factors such as smoking, alcohol consumption, poor nutrition, ill-fitting prosthesis, infancy, old age, or pregnancy [ 12 , 20 , 24 , 26 , 27 , 29 ].…”
Section: Oral Infections: Causative Pathogens and Aggravating Potentialmentioning
confidence: 99%
“…Dysgeusia typically occurs within 3-4 weeks of treatment and some studies have shown complete recovery within 3-12 months, depending on the volume of the irradiated tissues [6,12,15,16]. Especially moderate taste alterations start during the 2nd week of RT, involving 40% of patients, while severe dysgeusia is experienced from the 3rd week onward, reaching the peak of rate and severity of symptoms in the 5th week [11]. Unfortunately, some patients exhibit incomplete or no recovery even several years later [6,12,15,16].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Their side effects include a wide range of acute and late toxicities, such as orofacial pain, oral fibrosis and/or mucositis, dysphagia, dysgeusia, xerostomia, salivary impairments, osteonecrosis of the jaws, nausea, fatigue, and dermatitis. These alterations can become chronic issues and negatively influenced patients' quality of life (QOL) [6][7][8][9][10][11][12][13]. Taste disorders include hypogeusia (reduced taste sensation), ageusia (loss of taste sensation), dysgeusia (altered taste sensation), phantogeusia (taste alteration without external stimulus) and parageusia (distortion to a specific stimulus).…”
Section: Introductionmentioning
confidence: 99%